Exploration of solar photospheric magnetic field data sets using the UCSD tomography. Issue 12 (10th December 2016) - Jackson, B. V.; Yu, H.‐S.; Buffington, A.; Hick, P. P.; Nishimura, N.; Nozaki, N.; Tokumaru, M.; Fujiki, K.; Hayashi, K.
Abstract: This article investigates the use of two different types of National Solar Observatory magnetograms and two different coronal field modeling techniques over 10 years. Both the "open‐field" Current Sheet Source Surface (CSSS) and a "closed‐field" technique using CSSS modeling are compared. The University of California, San Diego, tomographic modeling, using interplanetary scintillation data from Japan, provides the global velocities to extrapolate these fields outward, which are then compared with fields measured in situ near Earth. Although the open‐field technique generally gives a better result for radial and tangential fields, we find that a portion of the closed extrapolated fields measured in situ near Earth comes from the direct outward mapping of these fields in the low solar corona. All three closed‐field components are nonzero at 1 AU and are compared with the appropriate magnetometer values. A significant positive correlation exists between these closed‐field components and the in situ measurements over the last 10 years. We determine that a small fraction of the static low‐coronal component flux, which includes the Bn (north‐south) component, regularly escapes from closed‐field regions. The closed‐field flux fraction varies by about a factor of 3 from a mean value during this period, relative to the magnitude of the field components measured in situ near Earth, and maximizes in 2014. This implies that a relatively more efficient process for closed‐flux escape occurs near solar maximum. We also compare and find that the popular Potential Field Source Surface and CSSS model closed fields are nearly identical in sign and strength. Key Points: Investigation of SOLIS and GONG data sets and their extrapolation to Earth in situ measurements using the UCSD IPS tomography technique Comparison of "closed" (near‐Sun) fields with those at Earth Comparison of CSSS and PFSS model closed fields